The Impact of Leadership Styles on Employee Innovative Performance: The Mediating Role of Innovative Behaviour in Saudi Manufacturing SMEs - Alharbi, Saad; Dato Mansor, Zuraina; Leong, Yee Choy (Advances in Social Sciences Research Journal, 2025)
This study investigates the differential effects of leadership styles on employee innovative performance within Saudi Arabia’s manufacturing SMEs, emphasizing the mediating role of employee innovative behaviour. Drawing on Path-Goal Theory, Cognitive Evaluation Theory, and Diffusion of Innovation Theory, the study examines the direct and indirect relationships between four leadership styles—transformational, autonomy-based, laissez-faire, and inclusive—and innovation outcomes. A quantitative methodology was adopted, utilizing structured survey responses from 374 leaders and managers across various regions. Data were analyzed using Structural Equation Modeling. Findings reveal that inclusive and transformational leadership significantly enhance innovative performance through their impact on employee innovative behaviour. In contrast, autonomy and laissez-faire styles show limited influence. The mediating role of innovative behaviour proves critical in translating leadership into performance outcomes. This study contributes theoretical insights into leadership and innovation and offers practical guidance for SMEs aiming to boost innovation in emerging markets.